Legal Reforms and Outcomes of the Action of Police Institutions in Combating Violence Against Women: A Systematic Review Protocol - Carlos Antonio Ferreira de Oliveira; Marcos de Moraes Sousa; Mara Célia Ferreira Ataide; Jéssica Traguetto; Woska Pires da Costa; Miguel de Matos-Torres (International Journal of Qualitative Methods)
Domestic violence (DV) against women in intimate relationships is a global public health issue with significant legal and institutional challenges. While legal reforms seek to enhance victim protection and perpetrator accountability, their implementation faces barriers within the criminal justice system, particularly in police and judicial institutions. A multi-agency approach—coordinating police, courts, social services, and NGOs—has emerged to improve institutional responses. This systematic review protocol follows PRISMA-P 2015 guidelines to assess the impact of legal reforms on DV policies within police institutions. A qualitative synthesis will analyse contextual factors, with searches conducted in Web of Science, Scopus, and MEDLINE/PubMed, complemented by citation mapping via Litmaps. The PICo framework and validated using the PRESS 2015 guided the search strategy, while PRISMA-S will inform data extraction and Rayyan will manage references. Independent reviewers will assess studies, resolving disagreements with a senior researcher. The review will evaluate legal reforms’ effects on DV recidivism, their effectiveness across contexts, and perceptions of punitive versus restorative approaches. Key challenges include resource constraints, institutional resistance, and program sustainability. Findings will support policymakers in refining legislative measures and strengthening institutional responses.